Regulating public sector wages in times of inflation and constitutional restraints - Brezovar, Nejc (Central European Public Administration Review, 2023)
Purpose: The article discusses the impact of public sector wages and inflation on various aspects of a country’s socioeconomic development. Methodology: Using Slovenia as a case study, the article focuses on how inflation impacts collective bargaining and wage regulation in the public sector, as well as the role of constitutional fiscal restraints in collective bargaining in the public sector. The research employs qualitative methods and focuses on patterns in existing documents and empirical case studies, and a comparative method involving Hungary. Findings and Academic contribution to the field: The article examines the impact of inflation on collective bargaining and wage regulation in the public sector. It concludes that inflation, even with (some) constitutional fiscal restraints in place, can affect collective bargaining and wage regulation in the public sector, depending on the bargaining power of unions and employers and specific provisions outlined in collective bargaining agreements and wage regulations.
Keywords: constitutional restraint; inflacija; inflation; javni sektor; public sector; sistem plač; ustavne omejitve; wage system